Analisis Usability Aplikasi Sistem Database Pemasyarakatan Menggunakan Use Questionnaire dan Pengaruh Usefulness, Ease of Use, Ease of Learning terhadap User Satisfaction Menggunakan Regresi Linier - Rachman, Arif; ETP, Lussiana (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2024)
The Directorate General of Corrections (Ditjenpas) has developed various Information Technology services, one of which is the Correctional Database System (SDP) Application. Until now, the development of the SDP Application has not ensured that the system can provide maximum benefits in managing and improving the effectiveness of the correctional system. Therefore, it is necessary to conduct a usability analysis of the SDP application based on user perceptions. In this study, an analysis of the usability of the SDP application was carried out using the USE Questionnaire method. The USE Questionnaire is an instrument commonly used to measure the usability of an application with four parameters, namely usefulness, ease of use, ease of learning, and user satisfaction. This study involved 100 respondents. The results of the instrument test showed that all questions were valid and reliable, so they could be used in the study. The measurement results of the entire USE Questionnaire variable were obtained from the respondent's score of 9,647 and the maximum score in this aspect was 11,200, so the percentage of feasibility was 86.13%. Thus, it can be concluded that the level of usability of the SDP application is categorized as "Very Feasible" for use in the correctional process.